Early vs late age at onset frontotemporal dementia and frontotemporal lobar degeneration. (20th March 2018) - Seo, Sang Won; Thibodeau, Marie-Pierre; Perry, David C.; Hua, Alice; Sidhu, Manu; Sible, Isabel; Vargas, Jose Norberto S.; Gaus, Stephanie E.; Rabinovici, Gil D.; Rankin, Katherine D.; Boxer, Adam L.; Kramer, Joel H.; et al.
Abstract : Objective: To examine clinicopathologic correlations in early vs late age at onset frontotemporal dementia (FTD) and frontotemporal lobar degeneration (FTLD). Methods: All patients were clinically evaluated and prospectively diagnosed at the UCSF Memory and Aging Center. Two consecutive series were included: (1) patients with a clinically diagnosed FTD syndrome who underwent autopsy (cohort 1) and (2) patients with a primary pathologic diagnosis of FTLD, regardless of the clinical syndrome (cohort 2). These series were divided by age at symptom onset (cutoff 65 years). Results: In cohort 1, 48 (25.3%) were 65 years or older at symptom onset. Pathologic causes of behavioral variant FTD (bvFTD) were similar in the early age at onset (EO) and late age at onset (LO) bvFTD groups. In corticobasal syndrome (CBS), however, the most common pathologic substrate differed according to age at onset: progressive supranuclear palsy (42.9%) in LO-CBS and Alzheimer disease (AD; 40.7%) in EO-CBS. In cohort 2, 57 (28.4%) were classified as LO-FTLD. Regarding FTLD major molecular classes, FTLD with transactive response DNA-binding protein of 43 kDa was most common in EO-FTLD (44.4%), whereas FTLD-tau (58.3%) was most common in LO-FTLD. Antemortem diagnosis of a non-FTD syndrome, usually AD-type dementia, was more frequent in LO-FTLD than EO-FTLD (19.3% vs 7.7%, p = 0.017). LO-FTLD was also associated with more prevalent comorbid pathologic changes. Of these, moderate to severe AD neuropathologic change and argyrophilic grain disease were overrepresented among patients who received an antemortem diagnosis of AD-type dementia. Conclusion: Patients with FTD and FTLD often develop symptoms after age 65, and age at onset represents an important consideration when making antemortem neuropathologic predictions.